Plan de negocios para una empresa que confecciona y comercializa ropa femenina especialmente para la mujer ejecutiva en Armenia “LADY’S S.A.S” (2012)
The business principal idea is to build a new small factory LADY´S that build and sell women clothes specially for executive women, exclusives designs, personal sellers and continuous schedule. Where the girls can find what they want, saving time and feeling better, finding clothes that they prefer, also when they want and have an excellent attention. We want to get into the local market, with a new continuous service, because in Armenia city there is not this kind of stores, there is no problem to go into, we will offer exclusives clothes and good quality, the idea is that the people meet our store and keeping in mind that today the women population has a big participation in working and there is not too much time for going to buy what they want, because the women is a very important part in the office. The target for this business plan, will be women between 20 and 45 years old, from stratum 2 of Quindio Department, having good strategies for marketing and not be a part of Quindio region only, then selling to all country and worldwide too.